Tinjauan atas Norepinephrine – First Line Vasopressor for Septic Shock - Martinova Sari Panggabean (Cermin Dunia Kedokteran, 2019)
Syok sepsis termasuk kedaruratan medis yang memerlukan resusitasi adekuat. Salah satu hal penting saat resusitasi awal adalah penggunaan vasoaktif untuk mencapai target MAP 65 mmHg sesegera mungkin. Terapi agen vasoaktif harus dimulai untuk mempertahankan tekanan arteri dan perfusi organ yang adekuat. Norepinephrine merupakan vasopressor pilihan pertama pada pasien syok sepsis. Septic shock is a life-threatening emergency that require adequate resuscitation. The use of vasoactive is important to achieve the 65 mmHg MAP target as soon as possible. Vasoactive agents should be initiated to restore adequate arterial pressure and organ perfusion. Norepinephrine is the first line vasopressor in patients with septic shock.